Seed priming with various chemical agents stimulates the germination and growth attributes synergistically in wheat (Triticum aestivum L.) varieties - Ghimire, Netra Prasad (2023)
Seed priming is a pre-sowing technique that involves the soaking of seeds in water or other solutions to initiate germination and early growth. This study explores the impact of different seed priming solutions on both the germinate on rate and overall performance of the wheat varieties Banganga and Bijaya. The seeds were subjected to different treatments, including polyethylene glycol (PEG) (10 %), boric acid (0.1 %), urea (2 %), polyethylene glycol (PEG) (5 %), ZnSO4 (2 %), MoP (2 %), DAP (2 %), CaCO3 (2 %), and with untreated seeds serving as the control. There was significant variation among the seed priming agents and that they also had a significant effect on the germination percentage, speed of germination, and seedling growth of wheat. CaCO3 (2 %), DAP (2 %), and untreated seeds were found to be the most effective priming solutions, showing superiority in all parameters measured, including shoot length, root length, and fresh weight. Furthermore, Bijaya exhibited higher germination parameters, while Banganga displayed better growth parameters. In conclusion, the findings suggest that using Bijaya with DAP (2 %) or CaCO3 (2 %) as seed priming agents can significantly improve the germination and growth parameters of wheat seedlings. This research sheds light on the potential of various chemical agents applied during seed priming to enhance the germination and growth of two different varieties of wheat.